Menjaga Akhlak Nasional: Kesadaran Tentang Pemahaman dan Memantau Perundungan - Taswiyah Taswiyah; Muhajir Muhajir; Nita Yuniarti (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2026)
The progress and decline of a nation depends on morality as a source of victory. However, Indonesia is currently facing a paradox: the advancement of information technology is not comparable to the decline in national morality, one of which is through the normalization of bullying. This research aims to formulate a strategy to prevent bullying by transforming spiritual values into sedentary character (Malakah). Using a qualitative approach of case studies, this study explores the process of internalizing the values of Muru'ah (self-respect) and Izzah (the glory of the nation) in the Islamic educational environment. The results show that bullying in Islamic boarding schools reflects a national moral crisis. External character education proved ineffective; the transformation of values into Malacca is needed through discipline, habituation, internalization, and crystallization. Teachers, parents, and the community play a key role in example and supervision. Without a strong moral foundation, the vision of a Golden Indonesia is difficult to realize because the generation is at risk of becoming oppressors or victims of bullying.